Modified expandable graphite and preparation method thereof, and modified polypropylene and preparation method thereof
By doping rare earth elements and grafting groups between the layers of expandable graphite, the problem that expandable graphite in the prior art is difficult to have excellent flame retardancy and halogen-free and non-toxic. , achieving high-efficiency flame retardant improvement and thermal stability improvement of polypropylene.
Patent Information
- Application Number
- CN202411685284.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-21
AI Technical Summary
In the prior art, expandable graphite is difficult to have excellent flame retardancy and is halogen-free and non-toxic, resulting in poor flame retardancy of polypropylene.
Modified expandable graphite is formed by doping rare earth elements such as Ce, Nd, Y and La to the surface between the layers of expandable graphite and grafting hydroxyl, alkyl and amino groups on the surface of the graphite layer. The modified expandable graphite forms a dense and solid barrier carbon layer by catalyzing the action of carbonization, thereby improving the flame retardant performance of polypropylene.
Modified expandable graphite has excellent flame retardant and thermal stability, which can effectively improve the flame retardant performance and heat resistance of polypropylene, meet the flame retardant requirements of various products such as automotive parts and home appliances, and is also halogen-free. Non-toxic and environmentally friendly advantages.
Smart Images

Figure CN119490696A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardant material preparation, and in particular to modified expandable graphite and a preparation method thereof, and modified polypropylene and a preparation method thereof. Background Art
[0002] Polypropylene is a typical general-purpose plastic with large production, wide application and low price. It has been widely used in electronic appliances, instrumentation, automobiles and construction industries. However, polypropylene and its composite materials are very flammable and emit a large amount of smoke and toxic gases during the combustion process, causing great harm to life, property and the environment, which greatly limits the application of polypropylene in electrical and electronic products, automotive industry and construction industry materials. Therefore, improving the flame retardant properties of polypropylene and its composite materials has always attracted extensive attention from researchers at home and abroad.
[0003] In order to improve the flame retardant properties of polypropylene, relevant research has been increasing in recent years to optimize its performance. At present, on the basis of halogen-free and environmentally friendly, a relatively effective method is to add an intumescent flame retardant. Compared with traditional halogen-free intumescent flame retardants, expandable graphite is a new type of halogen-free flame retardant, which has the characteristics of non-toxicity, less smoke, and excellent heat insulation, corrosion resistance, weather resistance, and durability, and has received widespread attention. However, in the prior art, when expandable graphite is used alone as a flame retardant, the barrier carbon layer formed after combustion is weak and fragile, which is difficult to meet the requirements of flame-retardant polypropylene.
[0004] On this basis, researching and developing a modified expandable graphite that has excellent flame retardancy and is halogen-free and non-toxic is of great significance for improving the flame retardancy of polypropylene. Summary of the invention
[0005] The main purpose of the present invention is to provide a modified expandable graphite and a preparation method thereof, and a modified polypropylene and a preparation method thereof, so as to solve the problem that expandable graphite in the prior art is difficult to have both excellent flame retardancy and halogen-free and non-toxicity, resulting in poor flame retardancy of polypropylene.
[0006] In order to achieve the above-mentioned object, the present invention provides a modified expandable graphite on one hand, which comprises expandable graphite and rare earth elements doped between the layers and on the surface of the expandable graphite; the expandable graphite comprises multiple layers of graphite, and the surface of at least one layer of the graphite layer is grafted with one or more groups of hydroxyl, alkyl and amino, and the rare earth elements are selected from one or more of Ce, Nd, Y and La.
[0007] Furthermore, the weight percentage of the groups on the surface of the graphite layer to the total weight of the expandable graphite is 0.5-2.0wt%.
[0008] Furthermore, the doping amount of the rare earth element is 1.5-5wt% based on the total weight of the modified expandable graphite.
[0009] Furthermore, the surface of the modified expandable graphite is also grafted with silane groups.
[0010] Furthermore, based on the total weight of the modified expandable graphite, the content of the silane group is 0.4-3wt%.
[0011] In order to achieve the above-mentioned purpose, another aspect of the present invention provides a method for preparing the modified expandable graphite provided by the present application, and the method for preparing the modified expandable graphite comprises: step S1, mixing expandable graphite with a solvent, adjusting the pH to 6-8, and obtaining a suspension containing expandable graphite; step S2, reacting the expandable graphite in the suspension with a rare earth element nitrate to obtain a first reaction product system; wherein the rare earth element nitrate comprises a rare earth element; step S3, performing solid-liquid separation on the first reaction product system, and obtaining the modified expandable graphite after drying.
[0012] Furthermore, between step S2 and step S3, the method further includes: subjecting the silane coupling agent to a chemical bonding reaction with the first reaction product system to obtain a second reaction product system, and step S3 includes: subjecting the second reaction product system to solid-liquid separation and obtaining modified expandable graphite after drying.
[0013] Furthermore, the temperature of the chemical bonding reaction is 60 to 120° C., and the time is 10 to 12 hours.
[0014] Furthermore, the chemical bonding reaction is carried out under stirring conditions, and the stirring speed is 300-400 r / min.
[0015] Furthermore, the weight ratio of expandable graphite to silane coupling agent is (97-100):(0.5-3).
[0016] Further, the silane coupling agent is selected from one or more of the group consisting of γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane.
[0017] Furthermore, the weight ratio of the rare earth element nitrate to the expandable graphite is 1:(4-20).
[0018] Furthermore, the rare earth element nitrate is selected from one or more of the group consisting of Ce(NO3)3·6H2O, Nd(NO3)3·6H2O, Y(NO3)3·6H2O and La(NO3)3·6H2O.
[0019] Furthermore, the solvent is a mixture of ethanol and water.
[0020] Furthermore, the solvent is an ethanol aqueous solution with an ethanol volume percentage of 10 to 30 vol%.
[0021] Furthermore, the mixing in step S1 is performed under ultrasonic conditions.
[0022] Furthermore, the ultrasonication time is 30 to 60 minutes.
[0023] Furthermore, step S3 comprises: filtering and washing the first reaction product system until the pH of the filtrate is 6-8, collecting the solid product, and drying the solid product to obtain modified expandable graphite.
[0024] Furthermore, the washing process is carried out using a washing liquid.
[0025] Furthermore, the washing liquid is an ethanol aqueous solution.
[0026] In order to achieve the above object, another aspect of the present invention provides a modified polypropylene, which comprises the modified expandable graphite and polypropylene provided in the present application.
[0027] In order to achieve the above object, another aspect of the present invention provides a method for preparing the modified polypropylene provided in the present application, the method for preparing the modified polypropylene comprising: melt blending polypropylene and modified expandable graphite, and sequentially subjecting the mixture to extrusion granulation and injection molding to obtain the modified polypropylene.
[0028] Furthermore, the weight ratio of polypropylene to modified expandable graphite is 85:(15-20).
[0029] Furthermore, the weight average molecular weight of polypropylene is 2.2×10 5 ~7×10 5 .
[0030] Furthermore, the temperature of the extrusion granulation is 150-200°C.
[0031] Furthermore, the injection molding temperature is 170-200°C.
[0032] Furthermore, a twin-screw extruder is used for extrusion granulation.
[0033] Furthermore, the screw speed is 150-250 rpm.
[0034] By applying the technical solution of the present invention, the expandable graphite itself has the characteristics of non-toxicity, less smoke, excellent heat insulation, corrosion resistance, weather resistance and durability, and it has a multi-layer graphite layer, which provides flexibility and elasticity for the expandable graphite, so that it can maintain a relatively stable structure when subjected to external forces. The introduction of the above-mentioned specific types of rare earth elements between the expandable graphite layers and on the surface can play its role in catalyzing carbonization, thereby facilitating the formation of a dense and solid barrier carbon layer, and thus making the modified expandable graphite have excellent flame retardancy. Moreover, the above-mentioned specific types of rare earth elements can cooperate with the expandable graphite to flame retardant, can suppress the "candle wick effect" produced when the expandable graphite is used as a flame retardant, form a denser flame retardant protective layer, and can increase the initial expansion temperature of the expandable graphite at the same time, and improve the flame retardant effect. In addition, the doping of the above-mentioned specific types of rare earth elements can also improve the thermal stability of the modified expandable graphite.
[0035] Applying the modified expandable graphite provided in the present application to the modification process of polypropylene can improve the flame retardancy and heat resistance of the modified polypropylene. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0037] Figure 1a The SEM image of the carbon layer morphology of Comparative Example 2 of the present application is shown;
[0038] Figure 1b The SEM image of the carbon layer morphology of Application Example 13 of the present application is shown;
[0039] Figure 2 The thermal stability performance curves of unmodified polypropylene or modified polypropylene in Application Comparative Example 1, Application Comparative Example 2 and Application Example 13 of the present application are shown, wherein curve a is the thermal weight loss curve of unmodified polypropylene in Application Comparative Example 1, curve b is the thermal weight loss curve of modified polypropylene in Application Comparative Example 2, and curve c is the thermal weight loss curve of modified polypropylene in Application Example 13;
[0040] Figure 3a The SEM image of the impact section of the modified polypropylene in Comparative Example 2 of the present application is shown;
[0041] Figure 3b The SEM image of the impact fracture surface of the modified polypropylene in Application Example 13 of the present application is shown. DETAILED DESCRIPTION
[0042] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0043] As described in the background technology, it is difficult for existing modified expandable graphite to have both excellent flame retardancy and halogen-free and non-toxicity, resulting in the problem of poor flame retardancy of polypropylene. In order to solve the above technical problems, the first aspect of the present application provides a modified expandable graphite, which includes expandable graphite and rare earth elements doped between the layers and on the surface of the expandable graphite; the expandable graphite includes multiple layers of graphite, and the surface of at least one layer of the graphite layer is grafted with one or more groups of hydroxyl, alkyl and amino, and the rare earth elements include but are not limited to one or more of Ce, Nd, Y and La.
[0044] Expandable graphite itself has the characteristics of non-toxicity, less smoke, excellent heat insulation, corrosion resistance, weather resistance and durability, and it has multiple layers of graphite layers, which provide flexibility and elasticity for expandable graphite, so that it can maintain a relatively stable structure when subjected to external forces. The introduction of the above-mentioned specific types of rare earth elements between the expandable graphite layers and on the surface can play its role in catalyzing carbonization, thereby facilitating the formation of a dense and solid barrier carbon layer, thereby making the modified expandable graphite have excellent flame retardancy. Moreover, the above-mentioned specific types of rare earth elements can cooperate with expandable graphite to flame retardant, can suppress the "candle wick effect" produced when expandable graphite is used as a flame retardant, form a denser flame retardant protective layer, and at the same time can increase the initial expansion temperature of expandable graphite and improve the flame retardant effect. In addition, the doping of the above-mentioned specific types of rare earth elements can also improve the thermal stability of modified expandable graphite.
[0045] Applying the modified expandable graphite provided in the present application to the modification process of polypropylene can improve the flame retardancy and heat resistance of the modified polypropylene.
[0046] In order to enhance the bonding force between expandable graphite and rare earth elements and further improve the flame retardancy of the modified expandable graphite, in a preferred embodiment, the weight percentage of the groups on the surface of the graphite layer to the total weight of the expandable graphite is 0.5-2.0wt%.
[0047] In a preferred embodiment, the doping amount of the rare earth element is 1.5-5wt% based on the total weight of the modified expandable graphite. The doping amount of the rare earth element includes but is not limited to the above range, and limiting it within the above range is conducive to better exerting its catalytic carbonization effect, thereby facilitating the improvement of the flame retardancy and thermal stability of the modified expandable graphite.
[0048] In a preferred embodiment, the surface of the modified expandable graphite is also grafted with silane groups. The grafting of silane groups can make the surface of the modified expandable graphite contain lipophilic groups, thereby helping to improve the compatibility of the modified expandable graphite and the polypropylene matrix. When the modified expandable graphite is used to modify polypropylene, it is helpful to improve the mechanical properties of the modified polypropylene.
[0049] In order to further improve the compatibility of expandable graphite with the polypropylene matrix and further improve the mechanical properties of the modified polypropylene, in a preferred embodiment, the content of the silane group is 0.4-3wt% based on the total weight of the modified expandable graphite.
[0050] The second aspect of the present application also provides a method for preparing the modified expandable graphite provided by the present application, and the method for preparing the modified expandable graphite comprises: step S1, mixing expandable graphite with a solvent, adjusting the pH to 6 to 8, and obtaining a suspension containing expandable graphite; step S2, reacting the expandable graphite in the suspension with a rare earth element nitrate to obtain a first reaction product system; wherein the rare earth element nitrate comprises a rare earth element; step S3, performing solid-liquid separation on the first reaction product system, and obtaining modified expandable graphite after drying.
[0051] The expandable graphite is mixed with a solvent and the pH is adjusted to the above range, which can improve the dispersibility of the expandable graphite, thereby facilitating subsequent processing. The expandable graphite in the suspension is reacted with a rare earth element nitrate, so that the rare earth element therein is doped between the layers and the surface of the expandable graphite to obtain a first reaction product system, in which the nitrogen atoms with high electronegativity in the rare earth element nitrate produce hydrogen bonds with the hydrogen atoms in the surface groups of the expandable graphite, and the expandable graphite can be surface modified. The first reaction product system is subjected to solid-liquid separation, and the liquid phase product containing impurities in the first reaction product system can be removed, and then dried to remove the solvent to obtain modified expandable graphite.
[0052] Expandable graphite itself has the characteristics of non-toxicity, less smoke, excellent heat insulation, corrosion resistance, weather resistance and durability, and it has multiple layers of graphite layers, which provide flexibility and elasticity for expandable graphite, so that it can maintain a relatively stable structure when subjected to external forces. The introduction of the above-mentioned specific types of rare earth elements between the expandable graphite layers and on the surface can play its role in catalyzing carbonization, thereby facilitating the formation of a dense and solid barrier carbon layer, thereby making the modified expandable graphite have excellent flame retardancy. Moreover, the above-mentioned specific types of rare earth elements can cooperate with expandable graphite to flame retardant, can suppress the "candle wick effect" produced when expandable graphite is used as a flame retardant, form a denser flame retardant protective layer, and at the same time can increase the initial expansion temperature of expandable graphite and improve the flame retardant effect. In addition, the doping of the above-mentioned specific types of rare earth elements can also improve the thermal stability of modified expandable graphite.
[0053] In a preferred embodiment, step S2 and step S3 further include: allowing the silane coupling agent to chemically bond with the first reaction product system to obtain a second reaction product system; and step S3 includes solid-liquid separation of the second reaction product system, and obtaining modified expandable graphite after drying. The silane coupling agent undergoes a hydrolysis reaction under the action of water to form silanol, which has active hydroxyl groups (-OH), so that they can undergo a condensation reaction with the oxygen-containing functional groups on the surface of the expandable graphite to form silicon-oxygen bonds (Si-OC), thereby achieving chemical bonding. The above-mentioned chemical bonding reaction can introduce lipophilic groups on the surface of the modified expandable graphite, which is beneficial to improving the compatibility of the modified expandable graphite with the polypropylene matrix, and then is beneficial to improving the mechanical properties of the modified polypropylene.
[0054] In order to improve the reaction efficiency of the chemical bonding reaction and increase the content of lipophilic groups on the surface of the modified expandable graphite, preferably, the temperature of the chemical bonding reaction is 60 to 120° C. and the time is 10 to 12 hours.
[0055] In a preferred embodiment, the chemical bonding reaction is carried out under stirring conditions, and the stirring speed is 300-400 r / min. The stirring speed includes but is not limited to the above range, and limiting it within the above range is conducive to improving the mixing uniformity of the reaction system, allowing the silane coupling agent and the expandable graphite to react more fully, thereby facilitating improving the chemical bonding efficiency.
[0056] In order to further improve the compatibility of the modified expandable graphite with the polypropylene matrix and further improve the mechanical properties of the modified polypropylene, the weight ratio of the expandable graphite to the silane coupling agent is (97-100):(0.5-3).
[0057] In a preferred embodiment, the silane coupling agent includes but is not limited to one or more of the group consisting of γ-glycidyloxypropyltrimethoxysilane (KH560), γ-aminopropyltriethoxysilane (KH550) and γ-methacryloxypropyltrimethoxysilane (KH570). Compared with other types, the use of the above silane coupling agent is conducive to improving the thermal stability of the modified expandable graphite, thereby facilitating its processing at high temperatures.
[0058] In a preferred embodiment, the weight ratio of rare earth element nitrate to expandable graphite is 1:(4-20). The weight ratio of rare earth element nitrate to expandable graphite includes but is not limited to the above range, and limiting it within the above range is conducive to better exerting the role of rare earth element catalysis into carbon, and is conducive to forming a denser and more solid barrier carbon layer, thereby improving the flame retardancy of the modified expandable graphite.
[0059] In order to improve the thermal stability of the modified expandable graphite, preferably, the rare earth element nitrate includes but is not limited to one or more of the group consisting of Ce(NO3)3·6H2O, Nd(NO3)3·6H2O, Y(NO3)3·6H2O and La(NO3)3·6H2O.
[0060] In order to improve the dispersibility of expandable graphite and facilitate the subsequent reaction with rare earth element nitrates, preferably, the solvent is a mixture of ethanol and water, and more preferably the solvent is an ethanol aqueous solution with an ethanol volume percentage of 10 to 30 vol%.
[0061] In a preferred embodiment, the mixing in step S1 is performed under ultrasonic conditions. Ultrasonic waves can produce strong mechanical vibrations and cavitation effects, and the mixing process under ultrasonic conditions is conducive to breaking up agglomerated particles, thereby improving the dispersibility of expandable graphite in the solvent.
[0062] In order to further improve the dispersibility of expandable graphite in the solvent, preferably, the ultrasonication time is 30 to 60 minutes.
[0063] In a preferred embodiment, step S3 comprises: filtering and washing the first reaction product system until the pH of the filtrate is 6 to 8, collecting the solid product, and drying the solid product to obtain modified expandable graphite. The first reaction product system is filtered and washed until the pH of the filtrate is 6 to 8. Compared with other ranges, limiting the pH of the filtrate to the above range is conducive to removing impurities and inhibiting the occurrence of side reactions during storage or further processing.
[0064] In order to further remove impurities and further suppress the occurrence of side reactions during storage or further processing, preferably, the washing process is carried out with a washing liquid, and preferably the washing liquid is an ethanol aqueous solution.
[0065] The third aspect of the present application also provides a modified polypropylene, which includes the modified expandable graphite and polypropylene provided in the present application. The modified expandable graphite provided in the present application can play a catalytic carbonization role due to the rare earth elements doped between the layers and the surface of the expandable graphite, and can form a more dense and solid barrier carbon layer. When it is used in the modified polypropylene, it can improve the flame retardancy of the modified polypropylene, thereby meeting the flame retardancy requirements of various products such as automotive parts and household appliances, and has the advantages of being halogen-free, non-toxic and environmentally friendly.
[0066] The modified polypropylene prepared in the present application has significantly improved carbonization ability, flame retardancy, thermal stability and impact resistance due to the efficient catalytic carbonization ability of the above-mentioned specific rare earth elements (Ce, Nd, Y and La), the synergistic flame retardant effect with expandable graphite and the improved compatibility of the modified expandable graphite with the polypropylene matrix.
[0067] In conclusion, applying the modified expandable graphite provided in the present application to modified polypropylene can improve the flame retardancy and heat resistance of the modified polypropylene.
[0068] The fourth aspect of the present application also provides a method for preparing the modified polypropylene provided by the present application, and the method for preparing the modified polypropylene comprises: melt blending polypropylene and modified expandable graphite, and sequentially extruding granulation and injection molding to obtain the modified polypropylene. Melting and blending polypropylene and modified expandable graphite can achieve uniform dispersion of polypropylene and modified expandable graphite at the molecular level, thereby improving the consistency of the modified polypropylene; the extrusion granulation process can prepare the mixture into uniform particles, which is convenient for subsequent injection molding processing, thereby improving production efficiency.
[0069] In order to improve the flame retardancy and heat resistance of modified polypropylene, preferably, the weight ratio of polypropylene to modified expandable graphite is 85:(15-20).
[0070] In a preferred embodiment, the weight average molecular weight of polypropylene is 2.2×10 5 ~7×10 5 The weight average molecular weight of polypropylene includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the performance and service life of the modified polypropylene.
[0071] In a preferred embodiment, the temperature of extrusion granulation is 150-200° C. The temperature of extrusion granulation includes but is not limited to the above range, and limiting it within the above range is conducive to improving the fluidity of the melt, thereby facilitating subsequent molding and cutting.
[0072] In order to shorten the molding cycle and thus improve production efficiency, preferably, the injection molding temperature is 170-200°C.
[0073] In a preferred embodiment, a twin-screw extruder is used for extrusion granulation. Using a twin-screw extruder for extrusion granulation can effectively disperse the modified expandable graphite, thereby improving its dispersibility in the polypropylene matrix, which is beneficial to improving the comprehensive performance of the modified polypropylene.
[0074] In order to further improve the distribution uniformity of the modified expandable graphite in the polypropylene matrix, preferably, the screw speed is 150-250 rpm.
[0075] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0076] The expandable graphite used in the examples and comparative examples was purchased from Qingdao Kangboer Graphite Products Co., Ltd. and had a size of 150 mesh.
[0077] (I) Preparation method of modified expandable graphite
[0078] Example 1
[0079] A method for preparing modified expandable graphite, comprising:
[0080] (1) 100 g of 150 mesh expandable graphite was mixed with 300 mL of solvent to obtain a mixed system, wherein the solvent was a mixture of ethanol and water in a volume ratio of 1:5, and the mixed system obtained was subjected to ultrasonic dispersion for 30 min; after heating to 120° C. under stirring, ammonia water was added dropwise to the mixed system, and the pH of the solution was adjusted to neutral to obtain a suspension containing expandable graphite, which was then used for standby;
[0081] (2) mixing 8 g of cerium nitrate hexahydrate Ce(NO3)3·6H2O with the above suspension under stirring conditions and reacting to obtain a first reaction product system;
[0082] (3) vacuum filtering and washing the first reaction product system until the pH of the filtrate is 7, collecting the solid product, and drying the solid product at 80° C. to obtain modified expandable graphite; wherein the washing is performed using a 20 vol% ethanol aqueous solution.
[0083] The doping amount of the Ce element is 2.6 wt % based on the total weight of the modified expandable graphite.
[0084] Example 2
[0085] The difference from Example 1 is that yttrium nitrate hexahydrate Y(NO3)3·6H2O is used to replace the cerium nitrate hexahydrate in step (2) and the amount of yttrium nitrate hexahydrate is changed so that the weight ratio of yttrium nitrate hexahydrate to expandable graphite is 1:4.
[0086] The doping amount of the Y element is 5wt% based on the total weight of the modified expandable graphite.
[0087] Example 3
[0088] The difference from Example 1 is that the amount of cerium nitrate hexahydrate in step (2) is changed so that the weight ratio of cerium nitrate hexahydrate to expandable graphite is 1:20.
[0089] The doping amount of the Ce element is 1.5 wt % based on the total weight of the modified expandable graphite.
[0090] Example 4
[0091] The difference from Example 1 is that the amount of cerium nitrate hexahydrate in step (2) is changed so that the weight ratio of cerium nitrate hexahydrate to expandable graphite is 1:30.
[0092] The doping amount of the Ce element is 1.1 wt % based on the total weight of the modified expandable graphite.
[0093] Example 5
[0094] The difference from Example 1 is that 2 g of KH560 is mixed with the first reaction product system obtained in step (2) and subjected to a chemical bonding reaction to obtain a second reaction product system, the second reaction product system is vacuum filtered and washed until the pH of the filtrate is 7, a solid product is collected, and the solid product is dried at 80° C. to obtain modified expandable graphite, wherein the temperature of the chemical bonding reaction is 120° C., the stirring speed is 400 r / min, and the time is 10 h.
[0095] Based on the total weight of the modified expandable graphite, the content of silane groups corresponding to KH560 is 1.5 wt %.
[0096] Example 6
[0097] The difference from Example 5 is that the weight ratio of expandable graphite to KH560 is 100:0.5.
[0098] Based on the total weight of the modified expandable graphite, the content of silane groups corresponding to KH560 is 0.4 wt %.
[0099] Example 7
[0100] The difference from Example 5 is that the weight ratio of expandable graphite to KH560 is 97:3.
[0101] Based on the total weight of the modified expandable graphite, the content of silane groups corresponding to KH560 is 2.5 wt %.
[0102] Example 8
[0103] The difference from Example 5 is that the weight ratio of expandable graphite to KH560 is 95:5.
[0104] The content of silane groups corresponding to KH560 is 4.1 wt % based on the total weight of the modified expandable graphite.
[0105] Example 9
[0106] The difference from Example 1 is that an equal amount of yttrium nitrate hexahydrate is used in step (2) instead of cerium nitrate hexahydrate.
[0107] The doping amount of the yttrium element is 1.8wt% based on the total weight of the modified expandable graphite.
[0108] Example 10
[0109] The difference from Example 5 is that silane coupling agent γ-methacryloxypropyltrimethoxysilane is used instead of KH560. The content of silane groups corresponding to γ-methacryloxypropyltrimethoxysilane is 1.7wt% based on the total weight of the modified expandable graphite.
[0110] Embodiment 11
[0111] The difference from Example 5 is that in step (1), the amount of expandable graphite is 150 g and the volume of the solvent is 350 mL; in step (2), the amount of cerium nitrate hexahydrate is 8 g; the stirring speed of the chemical bonding reaction is 300 r / min and the time is 11 h.
[0112] Based on the total weight of the modified expandable graphite, the doping amount of the Ce element is 1.7 wt %, and the content of the silane group corresponding to KH560 is 1.1 wt %.
[0113] Example 12
[0114] The difference from Example 5 is that in step (1), the expandable graphite is 150 g; in step (2), the cerium nitrate hexahydrate is 8 g, which is divided into four parts, one part is added to the suspension of step (1) every 10 minutes, and the pH is adjusted to neutral before each addition; the time of the chemical bonding reaction is 12 hours.
[0115] Based on the total weight of the modified expandable graphite, the doping amount of the Ce element is 1.6 wt %, and the content of the silane group corresponding to KH560 is 1.1 wt %.
[0116] Embodiment 13
[0117] The difference from Example 5 is that in step (1), the volume of the solvent is 350 mL, and the ultrasonic dispersion is 60 min; in step (2), the amount of cerium nitrate hexahydrate is 9 g, which is divided into three equal parts, and one part is added to the suspension of step (1) every 10 min, and the pH is adjusted to neutral before each addition; the time of the chemical bonding reaction is 12 h.
[0118] Based on the total weight of the modified expandable graphite, the doping amount of the Ce element is 2.9wt%, and the content of the silane group corresponding to KH560 is 1.5wt%.
[0119] Embodiment 14
[0120] The difference from Example 5 is that the temperature of the chemical bonding reaction is 100° C., the stirring speed is 300 r / min, and the time is 10 h.
[0121] Based on the total weight of the modified expandable graphite, the content of silane groups corresponding to KH560 is 1.4 wt %.
[0122] Comparative Example 1
[0123] The difference from Example 1 is that the expandable graphite is not modified, and commercially available expandable graphite is directly used.
[0124] Comparative Example 2
[0125] The difference from Example 5 is that step (2) is omitted and Ce(NO3)3·6H2O is not used; 2 g of KH560 is mixed with the suspension obtained in step (1) and a chemical bonding reaction is carried out.
[0126] Based on the total weight of the modified expandable graphite, the content of silane groups corresponding to KH560 is 1.6 wt %.
[0127] (II) Preparation method of modified polypropylene
[0128] Application Example 1
[0129] A method for preparing modified polypropylene, comprising:
[0130] (1) Polypropylene (weight average molecular weight 4.0×10 5 ) and the modified expandable graphite prepared in Example 1 of the present application, for standby use;
[0131] (2) melt-blending and extruding the polypropylene and modified expandable graphite weighed above in sequence using a twin-screw extruder to obtain pellets; wherein the extrusion granulation temperature of the twin-screw extruder is 200° C. and the screw speed is 150 rpm;
[0132] (3) The pellets are injection molded at a temperature of 200° C. to obtain modified polypropylene.
[0133] Application Examples 2 to 4
[0134] The difference from Application Example 1 is that the modified expandable graphite prepared in Examples 2 to 4 is used to modify the polypropylene respectively.
[0135] Application Example 5
[0136] The difference from Application Example 1 is that the modified expandable graphite prepared in Example 5 is used to modify the polypropylene.
[0137] Application Examples 6 to 10
[0138] The difference from Application Example 1 is that the modified expandable graphite prepared in Examples 6 to 10 is used to modify the polypropylene.
[0139] Application Example 11
[0140] The difference from Application Example 1 is that the modified expandable graphite obtained in Example 11 is used to modify the polypropylene; and the screw speed of the twin-screw extruder in step (2) is 200 rpm.
[0141] Application Example 12
[0142] The difference from Application Example 1 is that the modified expandable graphite obtained in Example 12 is used to modify the polypropylene; and the screw speed of the twin-screw extruder in step (2) is 250 rpm.
[0143] Application Example 13
[0144] The difference from Application Example 1 is that the modified expandable graphite obtained in Example 13 is used to modify the polypropylene; and the screw speed of the twin-screw extruder in step (2) is 180 rpm.
[0145] Application Example 14
[0146] The difference from Application Example 1 is that the modified expandable graphite prepared in Example 14 is used to modify the polypropylene.
[0147] Application Comparative Example 1
[0148] The difference from Application Example 1 is that no modified expandable graphite is added, and the polypropylene particles are directly injection molded.
[0149] Application Comparative Example 2
[0150] The difference from Application Example 1 is that the unmodified expandable graphite in Comparative Example 1 is used instead of the modified expandable graphite.
[0151] Application Comparative Example 3
[0152] The difference from Application Example 1 is that the modified expandable graphite prepared in Comparative Example 2 is used to modify the polypropylene.
[0153] The modified polypropylene prepared in the above-mentioned application examples 1 to 14 and the polypropylene or modified polypropylene prepared in the application comparative examples 1 to 3 of the present application were subjected to mechanical property tests, UL-94 vertical burning grade tests and limiting oxygen index tests, wherein the tensile strength was tested using the tensile property test method in GB / T 1040, the impact strength was tested using the notched impact strength test method in GB / T 1043, the limiting oxygen index value was tested using the limiting oxygen index test method in GB / T 2406, and the UL-94 vertical burning was tested using the test method in GB / T 2048. The test results are shown in Table 1.
[0154] Table 1
[0155]
[0156] Figure 1a and Figure 1b The morphology of the carbon layer after the UL-94 vertical combustion test of the application of comparative example 2 and the application of example 13 is shown respectively. From the scanning electron microscope image of the carbon layer morphology formed after the test sample is burned, it can be seen that there are many gaps and voids on the surface of the carbon layer of the test sample of comparative example 2, which is relatively loose and the expansion cracks are obvious and easy to fall off, and the continuity and density of the carbon layer are poor; while the carbon layer formed by the modified polypropylene prepared in the application example 13 is dense and continuous. This is because the presence of cerium in the modified expandable graphite achieves a good catalytic carbonization effect, which is conducive to the formation of a denser and more solid barrier carbon layer, so the formed carbon layer is relatively strong and not easy to fall off. Combined with the results shown in Table 1, it can be seen that the above-mentioned carbon layer can effectively prevent the expansion gas from escaping from the channel during the thermal expansion of ions at high temperature, inhibit the high-temperature decomposition of the matrix material, and thus better achieve the effect of protecting the internal material.
[0157] Figure 2The thermal stability performance curves of unmodified polypropylene or modified polypropylene in Application Comparative Example 1, Application Comparative Example 2 and Application Example 13 are shown, wherein curve a is the thermal weight loss curve of unmodified polypropylene in Application Comparative Example 1, curve b is the thermal weight loss curve of modified polypropylene in Application Comparative Example 2, and curve c is the thermal weight loss curve of modified polypropylene in Application Example 13. Figure 2 It can be seen that the initial decomposition temperature of curve b is delayed compared with that of curve a, while the initial decomposition temperature of curve c is higher, indicating that the thermal stability of the modified polypropylene prepared by Example 13 is greatly improved compared with that of Comparative Examples 1 and 2. In addition, the amount of residual carbon at high temperature is also a criterion for measuring the flame retardant performance of the material. The residual carbon formed after combustion can slow down the heat and mass transfer and stop the further degradation of the polypropylene matrix. Figure 2 It can be seen that at 600°C, curve c has the largest amount of residual carbon and has better heat resistance, which indicates that the modified polypropylene prepared in Application Example 13 has better thermal stability.
[0158] Figure 3a and Figure 3b The microscopic morphology of the impact fracture surface of the modified polypropylene prepared in the comparative example 2 and the example 13 are shown respectively. Figure 3a and Figure 3b It can be seen that the impact section of the modified polypropylene in Application Comparative Example 2 has relatively obvious voids left after the graphite is pulled out, and there is a relatively obvious gap between the interface of expandable graphite and polypropylene, and the interfacial adhesion is weak. This is because the inorganic expandable graphite surface cannot form good compatibility with the polypropylene matrix, and the interfacial adhesion is low; after being subjected to external forces, it is easier to form new cracks between the interfaces. However, the surface hydroxyl groups of the modified expandable graphite in the modified polypropylene in Application Example 13 can react with the polypropylene matrix to form chemical bonds, thereby enhancing the interaction between the modified expandable graphite and the polypropylene matrix, and reducing the effect of the modified expandable graphite as a flame retardant on the mechanical properties of the modified polypropylene. Figure 3b It can be seen that there is a strong interaction between the surface of the modified expandable graphite and the interface of the polypropylene matrix, and the interface is tightly bonded. Combined with the results shown in Table 1, it can be seen that the impact strength of the modified polypropylene is significantly improved.
[0159] From the above description, it can be seen that the above-mentioned application embodiment of the present invention achieves the following technical effects: expandable graphite itself has the characteristics of non-toxicity, less smoke, excellent heat insulation, corrosion resistance, weather resistance and durability, and it has multiple layers of graphite layers, which provide flexibility and elasticity for expandable graphite, so that it can maintain a relatively stable structure when subjected to external forces. The introduction of the above-mentioned specific types of rare earth elements between the expandable graphite layers and on the surface can play its role in catalyzing carbonization, thereby facilitating the formation of a dense and solid barrier carbon layer, thereby making the modified expandable graphite have excellent flame retardancy. Moreover, the above-mentioned specific types of rare earth elements can cooperate with expandable graphite to flame retardant, can suppress the "candle wick effect" produced when expandable graphite is used as a flame retardant, form a denser flame retardant protective layer, and at the same time can increase the initial expansion temperature of expandable graphite and improve the flame retardant effect. In addition, the doping of the above-mentioned specific types of rare earth elements can also improve the thermal stability of the modified expandable graphite.
[0160] In addition, the organophilic groups on the surface of the modified expandable graphite can significantly improve the compatibility of the expandable graphite with the polypropylene matrix.
[0161] Applying the modified expandable graphite provided in the present application to the modification process of polypropylene can improve the flame retardancy, heat resistance and impact resistance of the modified polypropylene.
[0162] As shown in Table 1, the UL-94 vertical combustion test level in application examples 1-14 all reached the V-0 test level, and the limiting oxygen index thereof was increased from 17.5% of the unmodified polypropylene to 27.8%; for the polypropylene modified with unmodified expandable graphite in application comparative example 2, it did not reach the flame retardant level in the UL-94 vertical combustion test, and the limiting oxygen index was also lower than that of the polypropylene modified with modified expandable graphite in the application examples; in addition, during the combustion experiment test, the application comparative example 1 burned very violently after ignition, producing a large amount of combustible droplets; the application comparative example 2 continued to burn after ignition, causing large-area combustion and not extinguishing; however, in the application examples of the present application, due to the effective protection of the formation of the carbon layer, no droplet phenomenon occurred, and after ignition, the combustion was extinguished in a very short time, with excellent flame retardant properties.
[0163] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A modified expandable graphite, characterized in that: The modified expandable graphite includes expandable graphite and rare earth elements doped between the layers and on the surface of the expandable graphite; the expandable graphite includes multiple layers of graphite, and the surface of at least one layer of the graphite layer is grafted with one or more groups of hydroxyl, alkyl and amino, and the rare earth elements are selected from one or more of Ce, Nd, Y and La.
2. The modified expandable graphite according to claim 1, characterized in that The weight percentage of the groups on the surface of the graphite layer to the total weight of the expandable graphite is 0.5-2.0wt%.
3. The modified expandable graphite according to claim 1 or 2, characterized in that: The doping amount of the rare earth element is 1.5 to 5 wt % based on the total weight of the modified expandable graphite; Preferably, the surface of the modified expandable graphite is also grafted with silane groups; More preferably, the content of the silane group is 0.4-3 wt % based on the total weight of the modified expandable graphite.
4. A method for preparing the modified expandable graphite according to any one of claims 1 to 3, characterized in that: The preparation method of the modified expandable graphite comprises: Step S1, mixing expandable graphite with a solvent, adjusting the pH to 6-8, and obtaining a suspension containing the expandable graphite; Step S2, reacting the expandable graphite in the suspension with a rare earth element nitrate to obtain a first reaction product system; wherein the rare earth element nitrate includes a rare earth element; Step S3, performing solid-liquid separation on the first reaction product system, and obtaining the modified expandable graphite after drying.
5. The method for preparing modified expandable graphite according to claim 4, characterized in that: The step S2 and the step S3 further include: subjecting the silane coupling agent to a chemical bonding reaction with the first reaction product system to obtain a second reaction product system, and the step S3 includes: subjecting the second reaction product system to the solid-liquid separation to obtain the modified expandable graphite after the drying; Preferably, the temperature of the chemical bonding reaction is 60 to 120° C. and the time is 10 to 12 hours; Preferably, the chemical bonding reaction is carried out under stirring conditions, and the stirring speed is 300-400 r / min; Preferably, the weight ratio of the expandable graphite to the silane coupling agent is (97-100):(0.5-3); Preferably, the silane coupling agent is selected from one or more of the group consisting of γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane and γ-methacryloxypropyltrimethoxysilane.
6. The method for preparing modified expandable graphite according to claim 5, characterized in that: The weight ratio of the rare earth element nitrate to the expandable graphite is 1:(4-20); Preferably, the rare earth element nitrate is selected from one or more of the group consisting of Ce(NO3)3·6H2O, Nd(NO3)3·6H2O, Y(NO3)3·6H2O and La(NO3)3·6H2O.
7. The method for preparing modified expandable graphite according to claim 4, characterized in that: The solvent is a mixture of ethanol and water, preferably the solvent is an ethanol aqueous solution with an ethanol volume percentage of 10 to 30 vol%; Preferably, the mixing in step S1 is performed under ultrasonic conditions, and the ultrasonic time is preferably 30 to 60 minutes; Preferably, the step S3 comprises: filtering and washing the first reaction product system until the pH of the filtrate is 6 to 8, collecting the solid product, and drying the solid product to obtain the modified expandable graphite; more preferably, the washing process is carried out with a washing liquid, and further preferably, the washing liquid is an ethanol aqueous solution.
8. A modified polypropylene, characterized in that: The modified polypropylene comprises the modified expandable graphite according to any one of claims 1 to 3 and polypropylene.
9. A method for preparing modified polypropylene according to claim 8, characterized in that: The preparation method of the modified polypropylene comprises: melt-blending polypropylene and modified expandable graphite, and sequentially performing extrusion granulation and injection molding to obtain the modified polypropylene.
10. The method for preparing modified polypropylene according to claim 9, characterized in that: The weight ratio of the polypropylene to the modified expandable graphite is 85:(15-20); Preferably, the weight average molecular weight of the polypropylene is 2.2×10 5 ~7×10 5 ; Preferably, the temperature of the extrusion granulation is 150-200°C; Preferably, the injection molding temperature is 170-200°C; Preferably, a twin-screw extruder is used for the extrusion granulation, and more preferably the screw speed is 150-250 rpm.